EFEKTIVITAS ECO-ENZYME LIMBAH KULIT PISANG KEPOK DALAM MENURUNKAN ANGKA LEMPENG TOTAL (ALT) KUMAN DI LANTAI - Fahrul Islam; Yesriely Dey Singa’; Abdul Ganing; Miftah Chairani Hairuddin (Poltekkes Kemenkes Bengkulu, 2026)
The problem of waste is one of the environmental issues that often becomes a public concern and has an impact on environmental damage. Kepok banana peels are one type of organic waste that can be utilized as a raw material in the production of natural floor-cleaning eco-enzymes. This study aims to determine the aroma, color, pH, and the composition of 300g, 450g, and 600g of kepok banana peel waste in reducing the total bacterial plate count on floors. The research method used is a sampling method with pretest and posttest designs. Floor swab samples were taken before and after the use of the eco-enzyme made from kepok banana peel waste. The results showed that the eco-enzyme had a typical acidic fermented smell, was yellowish-brown in color, and had a pH of 3.7–4. The eco-enzyme made from 300g of kepok banana peel waste was able to reduce the total bacterial plate count on the floor by 93%, 450g composition by 99%, and 600g composition by 56%. The LC50 value of the eco-enzyme composition from kepok banana peel waste in this study was 0.18g. The conclusion of this study is that the eco-enzyme with a concentration of 450g is the most effective formulation for reducing bacterial counts on floors. It is suggested that future research add fragrance ingredients to produce a more pleasant aroma.